Digital transformation of the administrative systems at a major South African university - Kotzé, Jacobus (University of the Free State, 2022)
Market and environmental changes have forced educational institutions to revisit their strategy for its administrative and learning systems. COVID-19 is just one example of how higher education institutions were forced to adapt to meet changing digital demands. Many institutions that considered themselves contact-only had to transform to administer digital and remote learning services (Yanckello 2019:1). Yanckello (2021:2) suggests that this somewhat forced digital transformation journey necessitated higher education organisations to re-evaluate their digital strategy; a strategy intended to take them from digital enablement through digital optimisation to digital transformation (Yanckello 2019:1). Even before the pandemic in 2019, many universities embarked on a mission to develop digital strategies. These strategies comes as a response to a shift towards using new technologies in higher education administration, and teaching and learning activities (Babington and McCusker 2018:3). Gartner also confirmed this in a recent study amongst technology decision-makers in the higher education domain (Yanckello 2019:3). Their research showed that 61% of respondents agree with the need for technological transformation to enable the organisation to meet its objectives and stay relevant in the higher education sector (Yanckello 2019:3). Digitalisation strategies in the context mentioned above are important when wanting to accommodate shifting demographics and changing expectations from staff and students (Yanckello 2021a:1). More importantly, however, is the task of sustained digital transformation to ensure that challenges faced today are effectively addressed and catered for in future capabilities (Yanckello 2021b:2). One such challenge universities face today comes from within and is the lack of vision, capabilities, and commitment to implement digital transformation strategies (Babington and McCusker 2018:3). These factors and the lack of progress in the digital transformation domain led Babington and McCusker (2018:3) to believe that the problem stretches beyond technology only. Babington and McCusker (2018:3) suggest that digital transformation can only be sustainable once sufficient support networks are put in place to address lacking digital literacy amongst students, staff, and academics. They further note (Babington and McCusker 2018:3) that far too many universities are still too obsessed with developing and implementing digital strategies instead of having a business strategy fit for a digital age. In this context, Yanckello (2021b:2) suggests that institutions should use the transformational power of digital as an opportunity. According to Yanckello (2021b:2), the transformative power of digital can be used as a lever to change business models and simultaneously address capabilities. Saunders (2019:2) note that although business models, capabilities, and strategy are the primary consideration for digital transformation, technology still plays a critical role. Technology and especially administrative system such as ERP (Enterprise Resource Planning), and SIS (student information systems), are essential enablers in delivering and supporting digital transformation of administrative systems (Saunders 2019:2).
Dissertation (MBA (Business Administration))--University of the Free State, 2022